PUSKESMAS READINESS IN ACCREDITATION IMPLEMENTATION AS EFFORTS TO IMPROVE THE HEALTH SERVICE QUALITY IN SUMBAWA DISTRICT - Rahmadhani, Nurul Saptorini; Ayuningtyas, Dumilah (Journal of Indonesian Health Policy and Administration, 2019)
. In achieving Universal Health Coverage in 2019, it is necessary to increase access and quality of health services to the community. Puskesmas accreditation is a method of improving the quality of service and patient safety as well as a condition to do collaboration with BPJS. According to Donabedian, quality of services needs to be supported by standardized structures, processes and outcomes which are oriented to internal and external customers. This study aims to analyze the readiness of Puskesmas in accreditation implementation as an effort to improve the quality of health services in Sumbawa Regency. This effort is an implementation act of Health Minister Regulation number 75/2014 on Puskesmas and number 46/2015 on FKTP accreditation by comparing it to those successful accreditation implementation of basic health services in various countries. This study design is a qualitative research uses the Rapid Assessment Procedure design, through in-depth interviews combined with literature review studies sourced from online data bases. This study result showed that the readiness of accredited Puskesmasin Sumbawa district wasseen from three aspects: (1) Structure: resources not yet fulfil the Permenkes 75/2014 standards, (2) Process: stages of the accreditation preparation process is in accordance with the guidelines, but the implementation was not optimal. (3) Outcomes: the accreditation implementation has positive impact on improving the quality of health services. It is necessary to evaluate the implementation of Puskesmas accreditation by involving the Community, the Health Office and the Regional Government.